1998
DOI: 10.1002/j.2161-0045.1998.tb00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Career Education Interventions: A Meta‐Analysis

Abstract: Twelve studies published between 1983 and 1996 that met the definitions for admissible studies established by Baker and Popowicz (1983) for a meta-analytic review of the effects of career education interventions were submitted to a similar meta-analytic integration. Effect sizes based on Glass's (1976) formula were determined for the current sample and were combined with the Baker and Popowicz (1983) sample, providing a sample of 30 studies and an overall effect size of 0.39.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…In fact, two meta-analyses (Baker & Taylor, 1998;Evans & Burck, 1992) demonstrated that career education interventions affect academic achievement, supporting the notion that students who can see the connections between school and their career paths are better prepared to succeed in school (Kenny, Blustein, Haase, Jackson, & Perry, 2006). Despite these empirical advancements, explanations as to why some students benefit, why some do not, or why some are affected at a higher level than others (in terms of school outcomes) remain to be fully understood.…”
Section: Vocational Exploration Racial Identity and School Engagementmentioning
confidence: 90%
“…In fact, two meta-analyses (Baker & Taylor, 1998;Evans & Burck, 1992) demonstrated that career education interventions affect academic achievement, supporting the notion that students who can see the connections between school and their career paths are better prepared to succeed in school (Kenny, Blustein, Haase, Jackson, & Perry, 2006). Despite these empirical advancements, explanations as to why some students benefit, why some do not, or why some are affected at a higher level than others (in terms of school outcomes) remain to be fully understood.…”
Section: Vocational Exploration Racial Identity and School Engagementmentioning
confidence: 90%
“…The National Association of Secondary School Principals). Although the implementation path has sometimes been bumpy, research tends to indicate the developmental advantages of the integration of career development related issues into the academic curriculum (Baker & Taylor, 1998;Evans & Burck, 1992;Magnum, 1998). A critical link in the translation of theory and policy into practice is the teacher at school.…”
Section: Socio-cultural Differences Between Jewish and Arab Teachers'mentioning
confidence: 98%
“…writing, decision-making, videos, role plays). Baker & Taylor (1998) concluded 'The relatively small number of published studies that were located may Downloaded by [95.85.80.143] at 18:58 04 June 2016 very well indicate that this is an underrepresented area of applied or field evaluation research ' (p. 383). Similarly, in their literature search of vocational psychology articles from 1987 to 1996, Worthington & Juntuneen (1997) found very few empirical studies that examined STW activities or related issues.…”
Section: The Need For Outcome-based Evaluationsmentioning
confidence: 95%
“…Few, if any, quantitative studies in this literature document and relate the student's participation in work-based learning programmes to expected outcomes of the STWOA. To illustrate, Baker & Taylor (1998), in their meta-analysis of the effects of career education interventions, identified only 12 evaluation studies between 1983 and 1996. These studies were characterised by relatively small sample sizes (only two were over 250), by short duration of implementation, by meeting the needs of specific student populations (e.g.…”
Section: The Need For Outcome-based Evaluationsmentioning
confidence: 99%